2010
DOI: 10.2147/tcrm.s4207
|View full text |Cite
|
Sign up to set email alerts
|

Role of tipranavir in treatment of patients with multidrug-resistant HIV

Abstract: The worldwide emergence of multidrug-resistant human immunodeficiency virus (HIV)-1 strains has the driven the development of new antiretroviral (ARV) agents. Over the past 5 years, HIV-entry and integrase inhibitor ARVs, as well as improved non-nucleoside reverse transcriptase inhibitors (NRTIs) and protease inhibitors (PIs), have become available for treatment. It is important to assess how these new ARVs might be most judiciously used, paying close attention to viral susceptibility patterns, pharmacodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In addition, various viral protease inhibitors can inhibit proteases and reduce HIV and HCV to undetectable levels which employ aspartyl and serine proteases, respectively. Some of these drugs are now being repurposed for the treatment of COVID-19, which is also possesses a MPP [23] , [24] , [25] , [26] , [27] , [28] . A computational drug repurposing study has previously shown that many more drugs including Lopinavir and Ritonavir (also HIV-1 protease inhibitors) are capable of inhibiting SARS-CoV MPP and, therefore, could serve as a homologous target, as the previous SARS-CoV main protease has 96.1% similarity to SARS-CoV-2 MPP [29] , [30] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, various viral protease inhibitors can inhibit proteases and reduce HIV and HCV to undetectable levels which employ aspartyl and serine proteases, respectively. Some of these drugs are now being repurposed for the treatment of COVID-19, which is also possesses a MPP [23] , [24] , [25] , [26] , [27] , [28] . A computational drug repurposing study has previously shown that many more drugs including Lopinavir and Ritonavir (also HIV-1 protease inhibitors) are capable of inhibiting SARS-CoV MPP and, therefore, could serve as a homologous target, as the previous SARS-CoV main protease has 96.1% similarity to SARS-CoV-2 MPP [29] , [30] .…”
Section: Introductionmentioning
confidence: 99%
“…Protease inhibitors are those drugs that can inhibit proteases and reduce levels of HIV and HCV to undetectable. Some of those drugs are now repurposing against the COVID-19, which is also a RNA virus and possesses the main protease [16][17][18][19]. Computational drug repurposing study previously showed Lopinavir and Ritonavir, two HIV-1 protease inhibitors were identified to be capable of inhibiting SARS-CoV main protease [20] that is why these the drugs used against HIV protease could be used as a homologous target as the previous SARS-CoV main protease has 96.1% of similarity with the SARS-CoV -2main protease [20].…”
Section: Introductionmentioning
confidence: 99%